2009
DOI: 10.1146/annurev.ento.54.110807.090626
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vector Control in the Global Program to Eliminate Lymphatic Filariasis

Abstract: Lymphatic filariasis (LF) is a major cause of acute and chronic morbidity in the tropical and subtropical parts of the world. The availability of safe, single-dose, drug treatment regimens capable of suppressing microfilaremia to very low levels, along with improvements in techniques for diagnosing infection, has resulted in the targeting of this major mosquito-borne disease for global elimination. The Global Program to Eliminate Lymphatic Filariasis (GPELF) was launched in 2000 with the principal objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
200
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(204 citation statements)
references
References 56 publications
2
200
0
2
Order By: Relevance
“…Of the 11 policy options recommended by the LF policy brief group, only 5 were accepted after the evidence synthesis. [51][52][53][54][55][56] These included the following: (i) Establishment of a standard protocol for diagnosis for LF; (ii) Vector control; (iii) Community directed distribution of long lasting insecticide treated bed-net (LLN) and Mectizan (Mass chemotherapy)/health education; (iv) Integrated control policy (onchocerciasis, schistosomiasis, and LF); and (v) Establishment of policy monitoring/evaluation (feedback mechanism)/with training and capacity building. The remaining options were rejected because of absence of sufficient evidence (Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 policy options recommended by the LF policy brief group, only 5 were accepted after the evidence synthesis. [51][52][53][54][55][56] These included the following: (i) Establishment of a standard protocol for diagnosis for LF; (ii) Vector control; (iii) Community directed distribution of long lasting insecticide treated bed-net (LLN) and Mectizan (Mass chemotherapy)/health education; (iv) Integrated control policy (onchocerciasis, schistosomiasis, and LF); and (v) Establishment of policy monitoring/evaluation (feedback mechanism)/with training and capacity building. The remaining options were rejected because of absence of sufficient evidence (Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…Mosquitoes of the Cx. pipiens complex are potential vectors of filarid worms in tropical and subtropical areas (Bockarie et al 2009) and diverse arboviruses, including West Nile virus (Apperson et al 2004, Cook et al 2006.Adult females and immature stages of the Cx. pipiens complex are morphologically similar.…”
mentioning
confidence: 99%
“…Among the sampled mosquitoes, we identified six genus with 16 species (2 species cannot be identified) during the period of study (Figure 3). Among the 16 species, Aedes vexans nipponii, which is active for seeking host specially in day time, and Culex pipiens pallens, generally nocturnal in behavior (Bockarie et al 2009), have shown highly dominant response (63.84% and 30.45%) towards CO 2 -baited Mos-hole trap. Trout et al (2007) and Trout and Brown (2009) also reported similar results that a majority of Aedes species were trapped under CO 2 -baited light traps (without the light), and traps under tree canopy catch more Culex species in CO 2 -baited light traps (without the No.…”
Section: Discussionmentioning
confidence: 99%